Kinetics of enforced carbonation of cement paste. (May 2020) - Zajac, Maciej; Skibsted, Jørgen; Durdzinski, Pawel; Bullerjahn, Frank; Skocek, Jan; Ben Haha, Mohsen
Abstract: The carbonation mechanisms of ground, hydrated cement pastes that mimic recycled concrete fines are investigated under direct wet carbonation. The carbonation is a sequential processes including dissolution of the hydrates, transport of the dissolved material to the precipitation sites and precipitation of the reaction products. During the first stages of carbonation, when portlandite reacts, the reaction is limited by the amount of dissolved CO2 and potentially by the calcite precipitation rate. When portlandite is depleted, the kinetics is dominated by the dissolution of other hydrates and diffusion of calcium into the solution. The main carbonation products are calcite and an alumina-silica (hydrate) gel. The hydrotalcite-like phase appears to be stable towards carbonation under the experimental conditions employed in this work. The CO2 concentration and the paste composition have a limited influence on the reaction mechanisms as well as on products formed.